The kaleidoscope model of policy change: Applications to food security policy in Zambia - Resnick, Danielle; Haggblade, Steven; Babu, Suresh Chandra; Hendriks, Sheryl L. (Elsevier, 2018)
What drives policy reform after long periods of policy inertia? What factors shape the effectiveness of policy implementation following reform decisions? These questions increasingly concern the international donor and research communities, given the importance of policy environments in shaping development outcomes and the growing need to achieve development impact with scarce resources. To address these questions, this paper introduces the Kaleidoscope Model of policy change.